Formule

The quick brown fox jumps over the lazy $ latex \frac{2}{3} a \cdot \alpha \pm 2\beta = \sqrt{\gamma}s=1$ dog \frac{2}{3}\, a\cdot\alpha\pm 2\beta=\sqrt{\gamma} The quick brown fox jumps over the lazy $ latex \frac{2}{3}\,a\cdot\alpha\pm 2\beta=\sqrt{\gamma}&s=2$ dog.

\frac{2}{3}\,a\cdot\alpha\pm 2\beta=\sqrt{\gamma}

The quick brown fox jumps over the lazy $ latex i\hbar\dfrac{\partial}{\partial t}\left|\Psi(t)\right>=H\left|\Psi(t)\right>&s=3$ dog.

i\hbar\dfrac{\partial}{\partial t}\left|\Psi(t)\right>=H\left|\Psi(t)\right>

The quick brown fox jumps over the lazy $ latex i\hbar\dfrac{\partial}{\partial t}\left|\Psi(t)\right>=H\left|\Psi(t)\right>&fg=3300ff&s=4$ dog.

i\hbar\dfrac{\partial}{\partial t}\left|\Psi(t)\right>=H\left|\Psi(t)\right>

The quick brown fox jumps over the lazy $ latex i\hbar\dfrac{\partial}{\partial t}\left|\Psi(t)\right>=H\left|\Psi(t)\right>&bg=ffcc00&s=4$ dog.

i\hbar\dfrac{\partial}{\partial t}\left|\Psi(t)\right>=H\left|\Psi(t)\right>

The quick brown fox jumps over the lazy $ latex i\hbar\dfrac{\partial}{\partial t}\left|\Psi(t)\right>=H\left|\Psi(t)\right>&bg=ffcc00&fg=3300ff&s=4$ dog.

i\hbar\dfrac{\partial}{\partial t}\left|\Psi(t)\right>=H\left|\Psi(t)\right>

The quick brown fox jumps over the lazy dog.

$ latex i\hbar\dfrac{\partial}{\partial t}\left|\Psi(t)\right>=H\left|\Psi(t)\right>&bg=ffcc00&fg=3300ff&s=4$

The quick brown fox jumps over the lazy dog.